An extension of Helson-Edwards theorem to Banach Modules - Sin-Ei Takahasi (International Journal of Mathematics and Mathematical Sciences)
An extension of the Helson-Edwards theorem for the group algebras to Banach modules over commutative Banach algebras is given. This extension can be viewed as a generalization of Liu-Rooij-Wang's result for Banach modules over the group algebras.